PENGARUH JOYFUL MATH GAME TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI PERKALIAN KELAS III SDN - Nila Rutbatul Ulya; Achmad Wahyudi; Ana Christanti; Machfudzil Asror (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the low mathematics learning outcomes of third-grade students at SDN Sudimoro on multiplication material, which was caused by the dominance of conventional teaching methods, resulting in students being less active and experiencing difficulties in understanding multiplication concepts. This study aimed to determine the effect of using the Joyfull Math Game on students’ learning outcomes in multiplication material. The study employed a quantitative approach using a pre-experimental research design with a One Group Pretest–Posttest Design. The research sample consisted of 30 third-grade students at SDN Sudimoro. Data were collected through pretest and posttest instruments that had been tested for validity and reliability. Data analysis was conducted using a normality test followed by the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed an improvement in the students’ mean score from 49.3 in the pretest to 77.66 in the posttest. The hypothesis testing yielded a significance value of 0.000 < 0.05, indicating that Ha was accepted and H₀ was rejected. Therefore, it can be concluded that the use of the Joyfull Math Game had a significant effect on students’ mathematics learning outcomes in multiplication material for third-grade students at SDN Sudimoro. The Joyfull Math Game can therefore be used as an innovative learning medium to improve mathematics learning outcomes in elementary school. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar matematika peserta didik pada materi perkalian di kelas III SDN Sudimoro yang disebabkan oleh pembelajaran yang masih didominasi metode konvensional sehingga peserta didik kurang aktif dan mengalami kesulitan memahami konsep perkalian. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan Joyfull Math Game terhadap hasil belajar peserta didik pada materi perkalian kelas III SDN Sudimoro. Penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian pre-experimental dan desain One Group Pretest–Posttest Design. Sampel penelitian berjumlah 30 peserta didik kelas III SDN Sudimoro. Teknik pengumpulan data menggunakan tes berupa pretest dan posttest dengan instrumen yang telah melalui uji validitas dan reliabilitas. Analisis data dilakukan melalui uji normalitas dan uji hipotesis menggunakan Wilcoxon Signed Rank Test karena data tidak berdistribusi normal. Hasil penelitian menunjukkan adanya peningkatan rata-rata nilai peserta didik dari 49,3 pada pretest menjadi 77,66 pada posttest. Hasil uji hipotesis memperoleh nilai signifikansi sebesar 0,000 < 0,05 sehingga Ha diterima dan H₀ ditolak. Dengan demikian, dapat disimpulkan bahwa penggunaan Joyfull Math Game berpengaruh signifikan terhadap hasil belajar matematika peserta didik pada materi perkalian kelas III SDN Sudimoro dan dapat digunakan sebagai alternatif media pembelajaran yang inovatif untuk meningkatkan hasil belajar matematika di sekolah dasar.